Estimation and synthesis of reachable set for delta operator systems. (May 2019) - Cui, Yukang; Shen, Jun; Cao, Guang-Zhong
Abstract: This paper considers the problems of reachable set estimation and synthesis of delta operator systems under bounded peak disturbances. A basic reachable set estimation tool for delta operator systems is developed, which can be reduced to the z -domain or s -domain forms when sampling period is 1 or tends to 0. Through the obtained generalized criterion of reachable set, the ellipsoidal reachable set estimation condition of delta operator systems is proposed. Moreover, the state-feedback controller design problem for delta operator systems is investigated. The intention of the controller is to bound the closed-loop system to a given ellipsoid or to make the reachable set of system trajectory as small as possible. Finally, the effectiveness of the obtained results are illustrated by several numerical examples.